Branding Indonesia with Agrotourism In Ciwidey Indonesia and Perth Australia - Sjarif, Safaruddin Husada; Yunus, Ulani; Limarandani, Ni Putu; Ramonita, Latifa; Shiong, Pong Kok (Ilomata International Journal of Social Science, 2024)
This study examines the implementation of Indonesian branding in the agrotourism sector in Ciwidey, Indonesia, and Perth, Australia. Agrotourism is chosen for its potential to introduce and promote Indonesia's natural resources, culture, and quality products to local and international tourists. Utilizing a qualitative method with a descriptive approach, the research involves case studies with open interviews and observed data collection. Data is gathered through interviews with key stakeholders and the study of materials related to the agrotourism industry in both locations, participant observation, content analysis, focus group discussions, data collection methods with semi-structured surveys and examining documents such as government regulations and promotional materials. Findings indicate that interactions between Indonesians and the Indonesian diaspora in Perth have positively influenced Indonesia's branding. The study highlights the importance of a unified strategy that integrates Ciwidey's agrotourism with the promotion of Indonesian culture in Perth. Real implications include developing a comprehensive marketing strategy, enhancing stakeholder engagement, implementing cultural exchange programs, improving visitor experiences, creating targeted marketing campaigns, increasing digital promotion and social media engagement, and promoting sustainable practices with community involvement. These actions can strengthen Indonesian branding in the agrotourism sector, enhance visitor experiences, and promote cultural exchange, ultimately boosting tourism and economic growth in both regions.